Proton wires via one-dimensional water chains adsorbed on metallic steps - Scipioni, R.; Donadio, D.; Ghiringhelli, L. M.; Delle Site, L. (Journal of Chemical Theory and Computation, 2011)
The process of proton transfer is here analyzed for one-dimensional water chains adsorbed on metallic steps. When the water chain contains a hydronium and a hydroxyl ion, two different mechanisms are possible, depending on the metal substrate. On coinage metals (Ag, Au), recombination is observed through a spontaneous Grotthuss mechanism. On more reactive surfaces (Pd and Pt), the hydronium ion is unstable and releases a proton that adsorbs onto the metal, leaving the negatively charged OH- unbalanced. In this case, the negative charge can be transferred along the wire with very low activation barriers. © 2011 American Chemical Society.
CRIS-Team Scopus Importer:2023-09-25